Pengaruh Lingkungan Kerja dan Fasilitas Kerja terhadap Kepuasan Kerja Karyawan Rumah Sakit Amalia Bontang - Berutu, Mutia Nur Fajriani Karina; Cindy, Rizki; Agus, Ikhwan (Masyarakat Ekonomi Syariah Bogor, 2024)
The selection of objects is caused by a decrease in Employee Job Satisfaction. Employee satisfaction is a set of employee feelings about their work, whether happy or like, or dislike or dislike, as a result of employee interaction with the environment or as a perception of mental attitudes, as a result of employee research related to their work. The overall work environment is the situation around the workplace, which will affect employees either directly or indirectly. Work Flexibility is a physical input that can be processed to produce the desired output (output). Organizational procedures will run smoothly if the facilities are very adequate, in good working condition, and well maintained. The total population is 240. The theories used to support research are theories of human resource management related to the work environment, work facilities and employee satisfaction. The research method used is a quantitative approach with a type of quantitative descriptive research. Data collection methods by interviews, distribution of questionnaires and documentation studies. The analysis method used is multiple linear regression using the SPSS application. coefficient of determination and testing simultaneously (F-Test) with values and partially (t-Test) and. The results showed that the work environment and work facilities simultaneously and partially had a significant positive effect on employee satisfaction.